Exploring the Role of Social Enterprises within the Romanian Welfare System - Petrescu, Claudia; Lambru, Mihaela (Calitatea Vieții, 2020)
Social enterprises are embedded in the local context, their organizational characteristics and operational strategies being influenced by the institutional settings, political culture and historical traditions and events. Similar to other European countries, Romania has included the modernization of the welfare systems in the development agenda of the last decade. One of the areas of interest was to better understand and promote the dynamics of the social enterprises as economic, social development actors and facilitators. From a neo-institutionalist perspective, this paper aims to explore the role of social enterprises as a component of Romanian welfare system. It starts with an overview of the history of the Romanian social enterprise, its roots and drivers; it continues with the identification of the roles, challenges and development processes of the social enterprises as welfare services.